Perianal Block: Is It as Good as Spinal Anesthesia for Closed Hemorrhoidectomies? - Jinjil, Kavitha (Anesth Essays Res, 2018)
BACKGROUND AND AIMS: This study compared if perianal block using ropivacaine and dexmedetomidine was as good as spinal anesthesia (SA) using bupivacaine (heavy) for closed hemorrhoidectomies. METHODS: A prospective randomized study was conducted in sixty patients who underwent closed hemorrhoidectomy. Thirty patients of Group A received SA. Thirty patients in Group B received local perianal block. Patients were evaluated for onset of the block, total pain-free period, and time to ambulation. Patient satisfaction in terms of pain during injection and satisfaction with the anesthesia technique was assessed after 2-week telephonically. Data were statistically analyzed using unpaired t-test for the continuous variables and Fischer's exact test for categorical variables. RESULTS: Onset of anesthesia was significantly earlier in Group B, mean (standard deviation [SD]) value being 3.17 (1.28) min as compared to Group A, 6.24 (4.28) min (P = 0.0004). Total pain-free period (mean [SD]) in minute was longer in Group B, 287 (120) min as compared to Group A, 128 (38) min. Time to ambulation was significantly earlier in Group B, 22.83 (29.32) min as compared to Group A 302 (92.41) min. Pain during injection between the two groups was comparable. However, more patients in Group B (60%) were satisfied with the anesthesia technique as compared to Group A (27.5%). CONCLUSION: Perianal block for hemorrhoidectomy with ropivacaine 0.2% using dexmedetomidine as an adjuvant is an effective and reliable technique which is as effective as SA. It provides prolonged postoperative analgesia and early ambulation.